Letter: inflammatory bowel disease and risk of myocardial infarction. Issue 6 (25th February 2020) - Wei, Bo; Wang, Junxue; Zhang, Yanda; Zhao, Jian
Abstract : LINKED CONTENT This article is linked to Choi et al paper. To view this article, visit https://doi.org/10.1111/apt.15446 .